2017
DOI: 10.1002/bio.3289
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanocluster‐enhanced luminol chemiluminescence for high‐selectivity sensing of tryptophan and phenylalanine

Abstract: A remarkable method for the highly sensitive detection of phenylalanine and tryptophan based on a chemiluminescence (CL) assay was reported. It was found that fluorescent copper nanoclusters capped with cysteine (Cys-CuNCs) strongly enhance the weak CL signal resulting from the reaction between luminol and H O . Of the amino acids tested, phenylalanine and tryptophan could enhance the above CL system sensitively. Under optimum conditions, this method was satisfactorily described by a linear calibration curve o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 34 publications
0
18
1
3
Order By: Relevance
“…[ 56 ] Moreover, recent findings indicate the presence of weak absorption bands around 350–375 nm in cysteine‐Cu NPs with size in the range 2–3 nm. [ 57,58 ] On the other hand, the broad band at 285 nm, obtained in the present study for Cu‐Cys samples with pH = 6, is red shifted with respect to measurements performed on much larger Cu‐Cys NPs (>20 nm), displaying an aborsoption band at 265 nm. [ 59 ] In a related investigation, using the glutathione peptide instead of cysteine amino acid as a protecting ligand, Cu NPs with average size around 5.5 nm display a smooth absorption spectrum with a shoulder at 230–260 nm, reminiscent of the quasicontinuous electronic band structure and quantum confinement effects of the metal NPs.…”
Section: Resultscontrasting
confidence: 50%
“…[ 56 ] Moreover, recent findings indicate the presence of weak absorption bands around 350–375 nm in cysteine‐Cu NPs with size in the range 2–3 nm. [ 57,58 ] On the other hand, the broad band at 285 nm, obtained in the present study for Cu‐Cys samples with pH = 6, is red shifted with respect to measurements performed on much larger Cu‐Cys NPs (>20 nm), displaying an aborsoption band at 265 nm. [ 59 ] In a related investigation, using the glutathione peptide instead of cysteine amino acid as a protecting ligand, Cu NPs with average size around 5.5 nm display a smooth absorption spectrum with a shoulder at 230–260 nm, reminiscent of the quasicontinuous electronic band structure and quantum confinement effects of the metal NPs.…”
Section: Resultscontrasting
confidence: 50%
“…In determining the essential amino acid Phe, optical methods were used, respectively: colorimetry [22,23]. UV and IR spectrophotometry [24], fluorescence [25][26][27][28][29], enhanced fluorescence [30], chemiluminescence [31][32][33]; separation methods, such as: gas chromatography [34], capillary electrophoresis, HPLC-high performance liquid chromatography [22,[35][36][37][38][39][40][41][42][43][44]; spectroscopic methods: Raman spectroscopy [45,46], laser-assisted spectroscopy [47], UV-Vis spectroscopy and chemometry [48]; UV−Vis and surface-enhanced Raman scattering [49], nuclear magnetic resonance [50] and circular dichroism spectroscopy [51]; mass spectrometry [22,34,41,52], fluorimetry [53].…”
Section: Instrumental Methodsmentioning
confidence: 99%
“…117 Another molecule that has often been used as a ligand is L-cysteine. Borghei et al [118][119][120] have shown that Cu NCs can rapidly be prepared in the presence of cysteine at pH = 12 at RT, which exhibited a PL emission in the range of 410 to 580 nm depending on the cysteine concentration. Su and Liu 121 employed L-cysteine with an equal molar ratio with Cu 2+ to prepare Cu NCs with a pale red emission color under UV irradiation (365 nm).…”
Section: Ligand Assisted Synthesis Of Cu Ncsmentioning
confidence: 99%